The autobiography of Mark Twain - Twain, Mark 1835-1910; Neider, Charles (Washington, D. C. : Office of English Language Programs, 2006)
The Autobiography of Mark Twain is the personal recollections of a great American author who wrote novels filled with adventure, humor, danger, and warmth. In these novels, he created characters that have become part of American culture: Tom, Huck Finn, Becky, Aunt Polly, and others
La Autobiografía de Mark Twain es el recuerdo personal de un gran autor estadounidense que escribió novelas llenas de aventura, humor, peligro y calidez. En estas novelas, creó personajes que se han convertido en parte de la cultura estadounidense: Tom, Huck Finn, Becky, tía Polly y otros.
Includes glossary
Keywords: NORTH AMERICAN LITERATURE -- AUTOBIOGRAPHY; LITERATURA NORTEAMERICANA -- AUTOBIOGRAFÍA; TWAIN, MARK